2009
DOI: 10.1007/s11249-009-9425-7
|View full text |Cite
|
Sign up to set email alerts
|

Wear Mechanisms at High Temperatures: Part 2: Temperature Effect on Wear Mechanisms in the Erosion Test

Abstract: In previous investigations on wear mechanisms at high temperatures made in High Temperature-Single Impact Test (HT-SIT) and High Temperature-Continuous Impact Abrasion Test (HT-CIAT), predominant wear mechanisms were identified and correlations to different material parameters could be presumed. In order to confirm these correlations, four different alloys which are promising to be used in high temperature applications like a sinter grate have been studied in the High Temperature-Erosion Test (HT-ET) by the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…However, abrasion resistance is also correlated to hardness, which changes with temperature. Resistance to high impact loads is not correlated to hardness [13,22]. Especially a microstructure containing coarse hard phases results in increased wear at high impact loads [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, abrasion resistance is also correlated to hardness, which changes with temperature. Resistance to high impact loads is not correlated to hardness [13,22]. Especially a microstructure containing coarse hard phases results in increased wear at high impact loads [13].…”
Section: Introductionmentioning
confidence: 99%
“…Especially a microstructure containing coarse hard phases results in increased wear at high impact loads [13]. Beyond a critical loading energy, which depends on the material, the wear rate increases significantly [22]. This threshold is not necessarily at the same energy for all temperatures, since materials often change their properties with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations show that in high temperature applications, several different wear mechanisms are relevant for the wear rate [13,[23][24][25]. It was shown that various material parameters influence the wear resistance, and some of these can be correlated to the wear rates under certain loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, abrasion resistance is also correlated to hardness, which is highly temperature dependent. Resistance to impact loads is not correlated to hardness [13,23]. But especially a microstructure containing coarse hard phases results in increased wear at high impact loads [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation